Willow production during 12 consecutive years—The effects of harvest rotation, planting density and cultivar on biomass yield. Issue 4 (16th December 2018) - Stolarski, Mariusz Jerzy; Szczukowski, Stefan; Tworkowski, Józef; Krzyżaniak, Michał; Załuski, Dariusz
Abstract: Willow biomass produced in short rotation coppice systems can potentially be used as biomass feedstock in Europe, the United States and Canada. However, most researchers focus on data from the first harvest rotation only, whereas multiple rotations have been rarely investigated. The aim of this study was to evaluate the effect of cultivar (5), planting density (12, 000–96, 000 cuttings/ha) and harvest rotation (annual, biennial, triennial) on willow biomass yields during 12 consecutive years in northern Poland. Every experimental factor and the interactions between factors significantly impacted willow yields. Biomass yield was highest in the triennial harvest rotation (13.3 Mg ha −1 year −1 ), 15.9% lower in the biennial rotation and 26.9% lower in the annual rotation. The highest average yield (14.6 Mg ha −1 year −1 ) was noted at a planting density of 24, 000 cuttings/ha, and yields were 9.3%–46.0% lower at the remaining densities. Cultivar UWM 095 had the highest average yield (13.0 Mg ha −1 year −1 ), whereas the yield of the remaining cultivars was 4.6%–32.4% lower. During the 12‐year period, yields were higher after the first harvest in annual, biennial and triennial harvest rotations. This above implies that high biomass yields can be obtained after the first harvest rotation if willows are cultivated on fertile soils at higher planting density, well managed and coppiced after the first year. However, yields are unlikely to be higher in successive harvest rotations, and they can even be lower, but more stable than in the first harvest rotation. Abstract : Research on willow production focuses on data from the first harvest rotation only, whereas multiple rotations have been rarely investigated. We evaluate the effect of cultivar (5), planting density (4) and harvest rotation (3) on willow yields during twelve consecutive years. The results show that high yields can be obtained after the first harvest rotation if willows are cultivated on fertile soils at higher planting density, well managed and coppiced after the first year. However, yields are unlikely to be higher in successive harvest rotations, and they can even be lower, but more stable than in the first harvest rotation.